Strategi Pemasaran Custom Decoration Untuk Masyarakat Generasi Y di Semarang - Vincentius Sutanto; Christian Anggrianto (Jurnal Vicidi, 2018)
This research was conducted in order to know about characteristic and consumer behaviour from the society so it correspond to precious decoration target market. Precious Decoration itself is a party decoration business with custom and personalized design concept, also with affordable price. One of them is called fabricated item. This Research was conducted with the combination between primary and secondary method which is qualitative, quantitative, and literature study approaches. The Qualitative was conducted by direct interviews with expert user, extreme user, and literature study. While quantitative distributed to men and woman with average age between. Through this research, it is expected that Precious Decoration business will had a segmented target market and had a great feedback for the future.